Hurdles in Management of Extra pulmonary Tuberculosis - Ahasan, HAM Nazmul; Bala, Chandra Shekhar (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Abstract not available J Bangladesh Coll Phys Surg 2016; 34(4): 182-183